2014
DOI: 10.1007/s10509-014-2069-6
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on the extended Chaplygin gas inflation

Abstract: In this paper, we study extended Chaplygin gas as a candidate for inflation and predict the values of gas parameters for a physically viable cosmological model. The extended Chaplygin gas which proposed recently has n + 2 free parameters. When n = 1, there are three parameters which are corresponding to modified Chaplygin gas. Here we focus on the second order equation of state where n = 2, so we have generally four free parameters. Under some assumptions, we reduced free parameters of the model to the only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…In recent years, some researchers made some studies on the thermal equation of state to MCG and found that it could cool down in some constraints of parameters [6]. To know more interesting results related to MCG, the readers are referred to [7][8][9][10][11][12]. If = 0, the system (1) becomes the homogeneous modified Chaplygin gas equations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some researchers made some studies on the thermal equation of state to MCG and found that it could cool down in some constraints of parameters [6]. To know more interesting results related to MCG, the readers are referred to [7][8][9][10][11][12]. If = 0, the system (1) becomes the homogeneous modified Chaplygin gas equations.…”
Section: Introductionmentioning
confidence: 99%
“…The Hayward black hole is an example of such a regular black hole as it does not contain a singularity at the center [23,24]. These black holes have been analyzed using various modifications of the Chaplygin gas formalism [25][26][27][28][29][30][31]. The motion of a particle in the background of a Hayward black hole also has been discussed [32].…”
Section: Introductionmentioning
confidence: 99%
“…So, some people proposed dynamical dark energy models such as scalar field models [7][8][9][10][11][12][13][14][15][16]. There are also another class of modified matter models based on exotic fluid so called Chaplygin gas and its extensions [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], which is indeed a way to unification of dark matter and dark energy. The other class of dynamical dark energy models are based on modification of the general relativity, which is called f (R) or F (R) gravity, where F is a function of the Ricci scalar and f = R + F [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%